FIRE AND URBAN ENVIRONMENT IN EARLY MODERN CITIES AND TOWNS OF CROATIAN AND SLAVONNIAN KINGDOM (Varaždin, Križevci, Koprivnica, Zagreb) - Petrić, Hrvoje (Array, 2009)
During the Early Modern Period, the most populated cities of Kingdom of Croatia and Slavonnia were the ones with royal privileges and the title of a free royal borough: Zagreb, Varaždin, Križevci and Koprivnica. These cities were densely populated within their urban cores, surrounded by city walls. Public and privately-owned buildings were mostly built of mud and wood, with straw roofs. Those building materials were highly flammable, catching up fire quickly. From the mid-Sixteenth century onwards, Koprivnica was a walled-in city, surrounded by bulwark, a fortress defending the border between the two empires: The Ottoman and the imperial Hapsburg. In 1559, Koprivnica was ravaged by fire, deliberately set off by a refugee from the Ottoman Empire ; this had a great damaging effect on the population, who fled destroyed city ; Koprivnica lost its central functions and suffered economic decline.In 1736, another great fire struck, destroying most of the houses in the centre and neighboring rural suburbs. Cities and towns mostly suffered from ravaging fires every 30 or so years. For example, Zagreb had great fires in 1624, 1645, 1674, 1706, 1731 and 1786. The biggest fire in Zagreb erupted in 1645, caused by a drunken student. The spreading of fire was greatly helped by high winds. Citizens and rural population from neighboring villages were robbed of their food, so the town authorities organized help in food and later on encouraged the use of bricks for building of homes and public buildings. However, this process lasted for decades. This also affected spatial dispersion of population and building of new streets with canals, providing water for fire extinguishing. Due to new building style, cities established brickyards, for manufacture of bricks and roofing tiles. In order to have some fire alert system, cities hired night watchmen, as early as the Seventeen century. The night watch servicemen were individuals, who would walk the streets at night and watch over possible sparks or fire. Cities also had numerous draw wells, providing water to extinguish fires. The Croatian government at the time (known as Croatian Royal Council) in 1771 decreed that all orders on fire be publicly read aloud at artisan guilds' meetings ; guild members were obliged to take action in case of fires, providing active support and help. The Croatian Royal Council decreed that houses be built of bricks ; also, the order specifically mentioned that chimneys be above rooftops. In 1776, the city of Varaždin, the capital city in the second half of Eighteenth century, was destroyed by great fire, caused by a boy smoking tobacco. The fire spread on by gunpowder explosion in the house of a merchant. The consequence was devastating - 62% city houses and half the houses in suburbs were burned down to the ground. After this great fire, the Croatian Royal Council moved the capital to the city of Zagreb, which has been the capital city ever since. Varaždin was decreed to build houses of bricks exclusively, which reduced the danger of having new fires. From the second half of Nineteenth century, there were firefighting volunteers brigades all over Croatia and Slavonnia (the very first one established in Varaždin in 1864).